Implementation of network management in child protection policy: Analysis of mobilization strategy in Makassar City - Islam, Firdha Nur; Alwi, Alwi; Syahribulan, Syahribulan (Edelweiss Applied Science and Technology, 2024)
This study aims to examine network management in the implementation of child protection policies in Makassar City, with a focus on mobilization strategies implemented by the Office of Women’s Empowerment and Child Protection (DP3A). The research method used is a qualitative approach with data collection techniques through interviews, observations, and document studies. Informants in this study include representatives from DP3A, Makassar Police, Institute for Public Policy Studies (LSKP), and other related institutions. The results show that the mobilization strategy implemented by DP3A Makassar City, which includes motivating and rewarding networks, utilizing digital platforms, and cross-sector collaboration, has succeeded in increasing the effectiveness of child protection policy implementation. This success is in line with network management theory. DP3A Makassar City has managed to gather and utilize various resources, strengthen cross-sector collaboration, and accelerate responses to child abuse cases. The use of digital platforms and continuous evaluation are also key factors in the success of child protection efforts in Makassar City. This research provides recommendations for strengthening inter-agency coordination and collaboration through the establishment of regular coordination forums, developing efficient information and data exchange mechanisms, and establishing an integrated referral system. Future research is expected to develop a network management model or framework that can be adapted and applied in the context of child protection at the local, regional and national levels in Indonesia.